Investment strategies for sustainable safe development of Chinese coal mine employees driven by digital intelligence - Yuan, Yuan; Cheng, Gang; Peng, Weicai; Yang, Xia; Du, Yamin (Frontiers in Public Health, 2024)
China’s “14th Five-Year Plan” proposes the construction of a “Digital China,” posing the challenge of digital transformation to coal mining enterprises. It is critical to compare the effectiveness of investing in digital devices with that of human capital. This study establishes a structural equation model based on the ‘regulation-situation-behavior’ theoretical framework. The model, developed through in-depth empirical analysis of enterprises, captures the relationships between exogenous and endogenous latent variables. The primary factors influencing both the active and passive safety behaviors of coal miners are discussed. The micro-mechanisms of human interaction with digital intelligence equipment are analyzed. The findings indicate that, in terms of overall utility value, investment in Intelligent surveillance management generates a total utility value that is 4.292 times higher than that of investment in team demonstration management. This disparity is primarily attributed to the significant positive impact that Intelligent surveillance management exerts on the active safety behavior of coal miners. Specifically, it influences miners’ safety behavior through the dual effects of situational promotion focus and situational prevention focus, whereas team demonstration management solely utilizes situational promotion focus. Additionally, the investigation reveals that miners attach significant importance to the role of instant feedback and continuous monitoring in Intelligent surveillance management. Consequently, coal mining enterprises should prioritize investing in digital intelligence supervision systems with real-time, full-time, and full-coverage capabilities. They should also focus on improving education, publicity, and training related to Intelligent surveillance management. These approaches can effectively enhance the digital, intelligent, safe and sustainable development capabilities of coal mines.